Ethical Considerations When Negotiating Entry in Community-Based Research. (1st July 2021) - Dubnewick, Michael; Wasyliw, Derek; Schaefer, Lee
Abstract: This manuscript focuses on our experiences of negotiating entry into two distinct research projects. The relational ethics of narrative inquiry acts as our conceptual underpinning as we inquire into the tensions we experienced as we negotiated who we were, and who we were becoming, in relation with the people we were living alongside. By reflecting on our storied experiences of negotiating entry our aim is to provide aspects that researchers can consider as they contemplate what it means to live in relationally ethical ways as we negotiate, and sustain, entry as researchers. Thinking with our experiences we share the following three considerations: (1) shifting from 'using' participants to 'becoming with, ' (2) becoming wakeful to how we step into the midst of ongoing lives, both personal and social, and (3) (re)naming our commitments as researchers.